Design of a sorting device with a barcode system based on Arduino Uno - Habibi, Farid; Eliza, Fivia; Mukhaiyar, Riki; Dewi, Citra (Department of Electrical Engineering Universitas Negeri Padang, 2025)
The development of technology in the industrial sector has experienced very rapid and advanced development at this time. In the production process in the industry, especially the sorting process, optimization is needed both from the performance and the results of the performance so that high work efficiency and maximum results can be obtained. So a goods sorting tool with a barcode system is needed as a tool that can sort goods automatically which is equipped with a barcode system to obtain information about the goods to be sorted so that it can make it easier for users to arrange goods according to what is desired. This goods sorting tool is equipped with a conveyor to move goods to the sorting place. This goods sorting tool method uses a barcode sensor that functions to detect the qr code on the goods, a weight sensor (loadcell) that functions to measure the weight of the goods, and an infrared sensor to detect the presence or absence of goods on the distribution line. After testing and analyzing the goods sorting tool with an Arduino Uno-based barcode system on the goods sorting system, the conclusion is that the goods sorting tool works well and the results achieved are in accordance with the function and work of the tool.